3D plotted PCL scaffolds for stem cell based bone tissue engineering - Yilgor, Pinar (2008)
The ability to control the architecture and strength of a bone tissue engineering scaffold is critical to achieve a harmony between the scaffold and the host tissue. Rapid prototyping (RP) technique is applied to tissue engineering to satisfy this need and to create a scaffold directly from the scanned and digitized image of the defect site. Design and construction of complex structures with different shapes and sizes, at micro and macro scale, with fully interconnected pore structure and appropriate mechanical properties are possible by using RP techniques. In this study, RP was used for the production of poly(e-caprolactone) (PCL) scaffolds. Scaffolds with four different architectures were produced by using different configurations of the fibers (basic, basic-offset, crossed and crossed-offset) within the architecture of the scaffold. The structure of the prepared scaffolds were examined by scanning electron microscopy (SEM), porosity and its distribution were analyzed by micro-computed tomography (m-CT), stiffness and modulus values were determined by dynamic mechanical analysis (DMA). It was observed that the scaffolds had very ordered structures with mean porosities about 60%, and having storage modulus values about 1!107 Pa. These structures were then seeded with rat bone marrow origin mesenchymal stem cells (MSCs) in order to investigate the effect of scaffold structure on the cell behavior; the proliferation and differentiation of the cells on the scaffolds were studied. It was observed that cell proliferation was higher on offset scaffolds (262000 vs 235000 for basic, 287000 vs 222000 for crossed structure) and stainings for actin filaments of the cells reveal successful attachment and spreading at the surfaces of the fibers. Alkaline phosphatase (ALP) activity results were higher for the samples with lower cell proliferation, as expected. Highest MSC differentiation was observed for crossed scaffolds indicating the influence of scaffold structure on cellular activities.